The Rise, Fall, and Readjustment of Telehealth: Effect of Coronavirus Disease 2019 on Its Use in an Academic Health Clinic - Shammout, Ali; Berry, Shamsi D.; Ziemkowski, Peter; Kroth, Philip J. (Applied Clinical Informatics, 2025)
Background The coronavirus disease 2019 (COVID-19) pandemic accelerated the adoption of telehealth. Long-term implications for continued telehealth use on a large scale in primary care are still emerging, and the key to this understanding is how telehealth adoption impacts the delivery of health care.Objectives Our objective was to quantify how telehealth adoption during the pandemic impacted patients' access to health care and the usage patterns of different access modalities (in-office, audio, and video).Methods This study analyzed 2 years of deidentified electronic health record data from the ambulatory clinics at a Midwest medical school from 2020 and 2021. We focused on patient demographics, primary diagnoses, and patient preferences for receiving health care throughout the COVID-19 pandemic.Results Of the 105,362 patient visits analyzed across in-office, audio, and video visits, demographic data varied by gender, age, and racial composition. During the early pandemic, telehealth usage peaked in April 2020, with audio and video visits accounting for 45.8 and 18.1% of the total visits, respectively. These rates declined to averages of 12.5 and 3.6%, respectively, over the following months. Primary diagnoses during telehealth visits are often related to COVID-19 exposure or mental health or behavioral issues. Lastly, statistically significant associations exist between the visit modality and primary diagnoses.Conclusion The COVID-19 pandemic initially saw a surge in audio telehealth visits; however, as safety measures were established, the mix of visit modalities returned to prelockdown levels. Video and audio telehealth maintained increased usage relative to prepandemic levels, potentially owing to increased awareness of the technology as a means for accessing health care and a learning curve associated with adoption. Patients preferred remote care during high COVID-19 transmission. Video telehealth has shown significant associations with psychiatric, behavioral, and neurodevelopmental diagnoses. Disparities in video telehealth use among racial groups have highlighted potential access issues.
Keywords: telehealth; COVID-19; health care trends; diagnostics; patient preferences